A Digital Watermarking Algorithm for Color Image Based on DWT - Huming Gao; Liyuan Jia; Meiling Liu (Institute of Advanced Engineering and Science, 2013)
An efficient digital watermark embedding algorithm for color image was presented in this paper, which is based on the discrete wavelet transform (DWT) and the spectral characteristics of human vision system. Firstly, three color separations was performed for color image, and color components of color image were transformed by DWT. Secondly, the embedding position of the watermark was confirmed by comparing the energy value of the low frequency sub-band in the transformed blue component and green component. Thirdly, the watermark was made Arnold Transform for encryption and was embedded in the color component with a larger power. Finally, this paper made the simulation experiments to evaluate the performance of the watermark. The simulation results showed that the embedded watermark had good invisibility and robustness for the common image processing, such as filtering, noise, especially compression and cropping. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2681